Toward educational testing reform: Inside reading achievement tests - Schutz, Dick (Education Policy Analysis Archives, 2013)
The commentary (1) uses the U. S. National Assessment of Educational Progress (NAEP) as a prototype for examining standardized reading achievement tests at the item level, and (2) sketches an alternative based on an initiative underway in the United Kingdom.